St. Jacob's Antwerp : art and Counter Reformation in Rubens's parish church - Muller, Jeffrey M. (Brill's studies in intellectual history, 2016)
Acknowledgements -- List of Illustrations -- List of Tables -- Abbreviations -- Introduction -- Chapter 1 St. Jacob's Parish and Construction of the Church: 1491-1780 -- Chapter 2 Ornament for the Church: 1585-1656 -- Chapter 3 Circa 1660: Crisis and Ornament: The Creation of a New Interior for the Parish Church -- Chapter 4 Sacraments in the Parish -- Chapter 5 The Blessed Sacrament Chapel and the Marriage Chapel -- Chapter 6 The Lady Chapel in Search of an Image -- Chapter 7 St. Jacob's New Collegiate Chapter of Canons and Their Choir -- Chapter 8 Private Chapels in the Church -- Chapter 9 St. Jacob's Counter Reformation Confraternities -- Chapter 10 Death in the Church -- Chapter 11 Church Against State in the Time of Enlightenment and Revolution -- Chapter 12 Conclusion -- Appendix 1 Documentation of Private Chapels in St. Jacob's -- Appendix 2 Foundation, Membership, Location of Brotherhoods at St. Jacob's in Chronological Order -- References -- Index